Resisting Institutional Power : The Women of St. Barnabas - Stylianou-Lambert, Theopisti; Bounia, Alexandra; Hardy, Sam Andrew (My University, 2014)
This article examines the relation between museums exhibiting sacred objects, visitors, and politics. More specifically, it explores the reasons why a minority group of visitors might resist, or even reject, the institutional power of a museum. St. Barnabas Icon Museum, located in the northern part of Cyprus, and a minority group of its visitors-the Women of St. Barnabas-serve as our case study. The two main communities of the island (Greek Cypriots and Turkish Cypriots) perceive the museum in dramatically different ways and use it to support their own claims. The Women of St. Barnabas, a group of Orthodox Christian, Greek Cypriot women, reject the museum and insist on using it as a religious instead of a secular space. The authors argue that apart from religious reasons, political beliefs predominantly shape this group's perceptions and uses of the museum.
Keywords: St. Barnabas icon museum; Cyprus; Orthodox christian; Greek cypriot